2011
DOI: 10.4414/smw.2011.13306
|View full text |Cite
|
Sign up to set email alerts
|

No need to search for the source of haematogenous arthroplasty infections

Abstract: From an epidemiologic point of view, patient history is the best way to predict the origin of PJI. Blind additional radiographic or endoscopic exams are costly, inconclusive and do not contribute to the management of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Eleven patients were intravenous drug abusers. In 148 episodes, the origin remained unknown despite intensive workup [25]. In 105 cases, patients were already under 35 different antibiotic regimens during joint sampling.…”
Section: Study Populationmentioning
confidence: 99%
“…Eleven patients were intravenous drug abusers. In 148 episodes, the origin remained unknown despite intensive workup [25]. In 105 cases, patients were already under 35 different antibiotic regimens during joint sampling.…”
Section: Study Populationmentioning
confidence: 99%
“…This is in agreement with the latest recommendations to avoid antibiotic prophylaxis in dental or endoscopic procedures [ 18 , 20 ]. Moreover, the fact that 70% percent of the patients with an unknown foci LAH PJI have been cured may suggest that identification and a extensive work-up may not be needed except for very specific cases such as Streptococcus bovis or Gemella morbillorum and their relationship with intestinal tumors [ 3 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the infection rate of hip and knee prosthesis is 1.9%, while the infection rate of open fracture xation is as high as more than 60% 2,3 . Staphylococcus aureus bacteremia is the primary cause of internal plant infections, but the study of Bouvet et al Show that the proportion of Gram-negative bacilli infection is higher than that of Gram-positive bacilli 2 years after implant 4,5 . Moreover, Escherichia coli is the primary cause of gram-negative bacteria IRI 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus bacteremia is the primary cause of internal plant infections, but the study of Bouvet et al Show that the proportion of Gram-negative bacilli infection is higher than that of Gram-positive bacilli 2 years after implant 4,5 . Moreover, Escherichia coli is the primary cause of gram-negative bacteria IRI 5,6 . The pathogenesis of IRI is complex and the treatment is extremely di cult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation